Development of HOTS Problem Based Learning Model Learning Tools to Improve Students' Critical Thinking Skills and Self-Efficacy - Al Karim, Dini Safitri; Asmin, Asmin; Sitompul, Pardomuan (Jurnal Perspektif, 2024)
This study examines the validity, practicality, and efficacy of HOTS-based problem-based learning (PBL) models to improve critical thinking skills and self-efficacy by using developed learning devices, students on critical thinking questions, and self-efficacy questionnaire sheets. This study uses a 4-D development model, namely Define, Design, Develop, and Desseminate. Grade VIII students became participants in this study. The results of the study showed that the learning devices were valid withÂ  an average validation result of the RPP of 3.4, student worksheets of 3.6, critical thinking ability tests of 3.8, and self-efficacy questionnaire sheets of 3.8. The problem-based learning approach containing HOTS questions such as RPP, LKPD, TKBK, and self-efficacy questionnaires was declared valid; usefulness the developed learning devices meet the criteria of experts and practitioners and can be used; the effectiveness of learning devices using problem-based learning models showed in the trial that 20% of students completed the pretest and 87% of students completed the posttest; The increase in critical thinking skills using the developed model reached 0.6 with a moderate category; Student self-efficacy was 80.1.